Study on the Main Factors of Frequency Variation of LC Resonant Prestress Detection Method - Benniu Zhang; Yuanyuan Zhao; Xingxing Li; Yanpeng Su; Qiang Yin; Jianhui Jiang (Advances in Materials Science and Engineering)
Stress loss of prestressed steel strands of existing bridges influences their bearing capacity, so it is of great significance to realize the stress detection. A steel strand that has an inductive property is designed into the resonant circuit, which can realize the stress measurement of the steel strands by testing the resonant frequency. This method is a promising approach for the stress detection of the steel strands. Previous research found that structural stress made the permeability of steel strands change due to the influence of magnetoelastic effect. In the process, the length of steel strands is also changed. Therefore, further research needs to be done to verify the main influence parameter affecting the resonant frequency of the circuit. Furthermore, it is very important to know how the stress affects the resonant frequency to realize the detection of the prestressed force of the steel strands. Therefore, in this paper, the relationship between stress and relative permeability and length is analyzed theoretically, and the theory of stress frequency of steel strands is modified and verified by experiments. The stress-frequency experiments of steel strands and aluminum strands with great difference in relative permeability are carried out. Experiments on stress frequencies of 7-Ф15.20 mm steel strands with different lengths are carried out. The influence of length and permeability parameters on resonance frequency is analyzed. The experimental results show that under the same conditions, the resonant frequencies of steel strands and aluminum strands are almost the same on LC electric circuits, and the resonant frequency decreases linearly with the increase of the natural length of the component and increases linearly with the increase of stress. Consequently, compared with the influence of length change on LC electromagnetic resonance frequency, the relative permeability of the stress change component can be ignored. The stress changes the resonant frequency mainly by changing the length of the strands.